PRODUK OLAHAN IKAN (PROKAN) UPAYA MENINGKATKAN INOVASI PRODUK PERIKANAN DI DESA SISARAHILI TELUK SIABANG, KECAMATAN SAWO, KABUPATEN NIAS UTARA - Manurung, Vindy Rilani; Anshori, Mohammad Auliya; Dalimunthe, Hilal Idama; Hardiananto, Muhammad Aditya; Manurung, Ferdiansyah; Aritonang, Bower Dynata; Tarigan, Yudi Pranata; Rahma, Febi Amelia; Nasution, Masniari; Naibaho, Risdo Elevri; Manurung, Aldian Morra; Ramadhan, Mhd Haikal; Sinaga, Justin Gibrant; Simangunsong, Rasyid Adri Arkana; Nurjannah, May Indah; Maharani, Putri (Universitas Mataram, 2024)
Sisarahili Village is one of the underdeveloped villages that has a lot of potential in the fisheries sector. Based on survey information in the village, the income and economy of the people of Sisarahili Teluk Siabang Village have decreased since the Covid-19 pandemic in 2020. The problem faced by the community in Sisarahili Teluk Siabang Village is the lack of knowledge and skills possessed by the community to process fishery products into processed fish products that are highly nutritious and have high selling value. In order to solve this problem, this service activity aims to provide knowledge and skills to the community in Sisarahili Teluk Siabang Village about the technology of processing fishery products into processed fish products (PROKAN) which are highly nutritious and can increase the income and economy of the community. The implementation method used to achieve the target of service activities is by conducting counseling, training on the technology of processing fishery products into Processed Fish Products (PROKAN): nuggets and meatballs and mentoring. The community group that is the special target of this service activity is fisherwomen. Through the Student Organization Capacity Strengthening Program (PPK ORMAWA), it becomes a student movement in providing knowledge about the technology of processing fishery products into Processed Fish Products (PROKAN). This community service activity was welcomed enthusiastically by the community by attending the counseling and training of Processed Fish Products (PROKAN). The community stated that they got additional insights and skills in processing fish into various products, namely nuggets and meatballs.